Revolutionizing Elder Care: AI-Powered Robotic Assistance in Skilled Nursing Facilities - Meghana Bhimavarapu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The convergence of artificial intelligence and robotics presents unprecedented opportunities to address growing challenges in long-term care settings, particularly skilled nursing facilities. As global populations age and healthcare worker shortages intensify, AI-driven robotic systems offer promising solutions by augmenting human caregiving capabilities. This article examines the current applications, benefits, implementation challenges, and future directions of AI-powered robotic assistance in eldercare environments. Current applications include mobility assistance and physical support systems that reduce caregiver injuries while increasing resident autonomy, companion robots that address loneliness and social isolation through engaging interactions, and health monitoring systems that enhance emergency response capabilities while enabling predictive healthcare approaches. Benefits include enhanced operational efficiency through task automation and resource optimization, improved quality of care through consistent protocol execution and personalization, and addressing workforce challenges by extending staff capabilities and reducing physical strain. Despite these benefits, implementation faces significant ethical concerns regarding human contact reduction, privacy, and equitable access; technical limitations in language processing, emotional recognition, and physical capabilities; and adoption barriers, including costs, staff acceptance, and regulatory uncertainties. Future directions suggest technological advancements in AI capabilities and physical design, emerging research in personalization, cultural adaptation, and hybrid care models; and necessary policy developments regarding standards, data management, reimbursement structures, and certification requirements. The integration of robotic caregiving represents a transformative approach that, when thoughtfully implemented, can enhance both caregiver effectiveness and resident quality of life.